WINTER BARLEY COLD-RESISTANCE AND PRODUCTIVITY DEPENDING ON SOWING TERMS AND RATES - Ярчук, І. І.; Божко, В. Ю.; Мороз, О. О. (Scientific Progress & Innovations, 2015)
This article presents the results of three-year field studies on the reaction of winter barley varieties for terms of sowing and seed rate in the Northern Steppe of Ukraine. The highest level of development in the autumn period have plants of early sowing. The article is mostly dedicated to the main disadvantage of winter barley – its poor resistance to low temperatures. Particularities of growth, winter-resistance forming and productivity are viewed in the light of hydrothermal conditions of a research year.